The feasibility of use of sweet potato (ipomoea potatoes l.) flour in the preparation of bakery products (Research, Society and Development, 2020)
Sweet potatoes are one of the most consumed vegetables in Brazil and in the world, as they are cheap, easy to buy and healthy food. The objective of this work was to prepare sweet potato flour, bread with the addition of sweet potato flour and evaluate its effect. Four bread formulations were prepared: P0% (standard) and the others added potato flour of 8% (P8%), 16% (P16%) and 24% (P24%). The microbiological, physical-chemical, sensory parameters and the color of flour and bread were evaluated. A statistical analysis was performed with the averages by the Tukey test at 5%. The result of the microbiological analysis was in accordance with the legislation. In potato flour, components such as carbohydrates and proteins stood out. Bread samples showed a significant difference (